Dinesh Tahiliani

Ranch Hand

Posts: 486

Ireneusz Kordal

Ranch Hand

Posts: 423

posted 8 years ago

In the expression a || b, first left side (a) is evaluated, and if it is 'true', then the right side is skipped, because for a || b, if only a=true then the whole expression is true.

Simillary for a && b, if a=false, then only only the left side (a) is evaluated (executed) and (b) is skipped.

This is not true for a | b and a & c expressions - in these cases compiler always evaluates boths sides (a and b).

So, look how the 'for' loop is executed:

1. z = 0, x = 0, y = 0

++x > 2 (x=1) --> false, ++y > 2 (y=1) -->false

2. z = 1, x = 1, y = 1

++x > 2 (x=2) --> false, ++y > 2 (y=2) -->false

3. z = 2, x = 2, y = 2

++x > 2 (x=3) --> true!! - so don't evaluate ++y > 2 (y=2)!!

whole if condition is true --> execute x++ (x=4)

4. z = 3, x = 4, y = 2

the same as point 3 - x is incremented twice, and y is unchanged

5. z = 4, x = 6, y = 2

the same as in 3 - x is incremented twice, and y is unchanged

in the end, z=5, x=8 and y=2

[ June 23, 2008: Message edited by: Ireneusz Kordal ]

Simillary for a && b, if a=false, then only only the left side (a) is evaluated (executed) and (b) is skipped.

This is not true for a | b and a & c expressions - in these cases compiler always evaluates boths sides (a and b).

So, look how the 'for' loop is executed:

1. z = 0, x = 0, y = 0

++x > 2 (x=1) --> false, ++y > 2 (y=1) -->false

2. z = 1, x = 1, y = 1

++x > 2 (x=2) --> false, ++y > 2 (y=2) -->false

3. z = 2, x = 2, y = 2

++x > 2 (x=3) --> true!! - so don't evaluate ++y > 2 (y=2)!!

whole if condition is true --> execute x++ (x=4)

4. z = 3, x = 4, y = 2

the same as point 3 - x is incremented twice, and y is unchanged

5. z = 4, x = 6, y = 2

the same as in 3 - x is incremented twice, and y is unchanged

in the end, z=5, x=8 and y=2

[ June 23, 2008: Message edited by: Ireneusz Kordal ]

Don't get me started about those stupid light bulbs. |